PITY AND SWORD: POLITICIZATION OF COMPASSION IN THE ECCLESIASTICAL DISCOURSE OF THE HIGH MEDIEVAL PERIOD - Галена, Евгений (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
The article examines how the politicization of compassion in the 11th — 3th centuries led to an escalation of violence throughout Europe. The author demonstrates that the changes in Christian piety during the High Middle Ages reflected in both theology and iconography influenced the formation of a new understanding of compassion. At the same time, the Catholic Church has supported these changes, as it allowed the Church to strengthen its position in the struggle for political power against secular rulers. The article shows that compassion became a part of the politics of victimhood, which the Church used in the conflict with the State